Nonviolence and Power in The Ottawa Panhandlers' Union - Lamarche, Teague (University of Ottawa (Canada), 2010)
The Ottawa Panhandlers' Union's use of nonviolent action provides a useful case to examine the relationship between nonviolence, power and truth. Dahl, La Boetie and Foucault's theories of power provide different perspectives from which to analyze the use of nonviolence by the OPU. Dahl and La Boetie's theories of power as capacity and consent respectively focus on the OPU's ability to force others to take particular actions, and choice in compliance in scenarios imposed by others. Alternately, Foucault's theory of power allows an examination of the union members' positions within power relations, and how tacit social understandings construct their knowledge of themselves and others. When the OPU's use of nonviolence is seen in this light, addressing positions within power relations, and identifying the tacit social understandings that construct them, become important elements in understanding nonviolent action. Keywords: Nonviolence, Power, Foucault, Truth, Panhandlers
Keywords: Philosophy.